Part III: Digestibility of eight hybrid sorghum grains and three hybrid corns - McCollough, R.L.; Brent, B.E. (Kansas State University. Agricultural Experiment Station, 2011)
Apparent coefficient of digestion (COD) was determined for eight hybrid sorghum grains and three hybrid corns named in Part I.
Keywords: Beef; Digestibility; Hybrid sorghum; Hybrid corn